Reformulasi Strategi Pemasaran Bengkel Otomotif Mengunakan Metode SWOT Dan QSPM - Achmad Maulana Abdillah; Nina Aini Mahbubah; Akhmad Wasiur Rizky (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2021)
The rised in number of four-wheeled vehicles in Indonesia has a positive impact on elevating business opportunities for otomotive repair services. This type of business is reside in all over region with service level vary from conventional services to advance services. Hari Jaya Teknik is a medium-sized service enterprise which focus on otomotive repairements in Gresik city. The business is experiencing with decreasing customers’ demand caused by conventional business promotion techniques and a number of business competition around bussiness location. This study aims to reformulate a marketing strategy to maintain the existence of a business that has been built for more than twenty years. SWOT and QSPM are the approaches used in this study. The research method begins by identifying internal and external factors obtained from six expert respondents, followed by the calculation of the SWOT and QSPM matrix. The results of this study found eight factors as primary consideration in order to redevelop marketing strategy. The highest factor namely strategy to both maintain and enhance the quality of service. These factors followed by calculating reasonable service costs in order to maintainbussiness reputation as well as customer loyalty. The reformulation of the eight strategies is also expected to be able to bring in new customers in the workshop in order to sustaining bussiness existence.